Integrasi Spiritualitas dan Kecerdasan Digital dalam Desain Pembelajaran Pendidikan Agama Islam di Perguruan Tinggi - Fauzan, Muhammad; Gusmaneli, Gusmaneli (Lembaga Yasin AlSys, 2025)
The rapid advancement of digital technology has brought significant transformation to the field of education, including in the teaching of Islamic Religious Education (PAI) at the higher education level. Nevertheless, this digital progress must be balanced with the strengthening of spiritual aspects to ensure that the learning process retains the essence of Islamic values. This study aims to examine the concept of integrating spirituality and digital intelligence in the instructional design of PAI within universities. A qualitative approach was employed through literature analysis and conceptual studies of various technology-based learning models grounded in Islamic values. The findings indicate that the integration of spirituality and digital intelligence can be realized through instructional designs that combine interactive digital technology with spiritual-reflective approaches. These strategies include the use of digital media embedded with ethical values, the implementation of spiritually based project learning, and the reinforcement of Islamic digital literacy competencies. The study confirms that such integration not only enhances the effectiveness of learning but also contributes to shaping students with strong faith, noble character, and adaptability to technological developments.